Analyse spectrale des filtres de la méthode de désaisonnalisation X-11-ARMMI - Cholette, Pierre (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractThis paper examines the changes produced on the seasonal estimates of the X-11-ARIMA method (Dagum, 1980), when (1) the two by twelve preliminary trend-cycle estimator is replaced by that of Cholette (1979a) (now optional in the program) and when (2) the "end" weights of the seasonal three by three and three by five moving averages are modified.The results show that the first substitution has a small but desirable effect which becomes more substantial for short series and for those with fast cyclical movements. On the other hand, the suggested replacement of the seasonal end weights would entail considerable improvements for series with stable seasonality or with much irregularity. Both modifications do not affect the properties of X-11-ARIMA in the "centre" of long series.